Sound symbolism and the perception of luxury versus basic brands - Abhishek Pathak (2015)
Globalization has witnessed a massive surge in consumerism and with it, the rise of global super brands. Brands, which act as shortcuts to consumers, reassuring them of specific qualities and deliverables, are now bigger than ever before in human history. But in this cluttered brand saturated environment, how can manufacturers of new products position and launch their brands in such a way as to immediately attract consumer’s attention? One key component is the nomenclature itself, i.e. the novelty and importance of the brand name. Today, most companies recognizing the relevance of this employ branding agencies and consultants to create novel brand names derived from the aspirations of the products in question. But not all of these new product launches succeed and some estimate that between 40-90 % of all new products launched fail within their first year (Gourville, 2006), with the brand name identified to be one of the factors behind their failure (for example, Ford Edsel; Klink, 2001). So what is the secret behind the naming of a new product or brand and is there a specific recipe for success? This dissertation explores the use of sound symbolism in luxury and basic brand names to investigate whether there is a phonetic recipe that signals whether brands are either premium or essential and how this might work in consumers’ minds. The sound of a spoken word conveys meaning to the listener. All spoken words are composed of basic sound units called phonemes and past research has shown that an individual phoneme itself, even if embedded within a fictitious word, can influence human emotions. This dissertation has investigated a novel phenomenon: the effect of different phonetic structures on the perception of hypothetical luxury and basic brand names. Specifically, it was hypothesized that the phonetic structures of luxury brand names are distinct from those of basic brand names and that these distinctions help to maintain the perception of exclusivity associated with luxury brands in consumers’ minds. The hypothesis was tested using three approaches- Firstly, phonetic differences in the written form of a set of existing luxury and basic brand names were explored using the International Phonetic Alphabet (IPA) notations; secondly, a spectral analysis of the acoustic wave pattern differences between luxury and basic brand names was carried out and thirdly, in a semantic priming reaction time study, potential differences in the implicit perception of hypothetical luxury and basic brand names (generated using the distinct phonetic patterns associated with luxury and basic brands and identified in Studies 1 and 2) were investigated. The results indicate that the phonetic structures of luxury and basic brand names differ in their use of back/front vowels, stressed/unstressed vowels, the presence/absence of affricates and their syllabic structure. Results of the semantic priming experiment suggest that the use of these specific phonetic characteristics can enhance the perception of ‘luxury-ness’ or ‘basic-ness’ in a brand name. Furthermore, as the effect is demonstrated using an implicit semantic priming paradigm, it is indicative of the automatic and implicit nature of these manifestations. In the first section, this dissertation demonstrates that despite their premium appeal, luxury brand names tend to use some of the more unconventional patterns of human speech, which deviate from everyday speech patterns and are even considered to evoke negative perceptions. The results suggest that even unfamiliar phonetic patterns such as those contained in a hypothetical name (as opposed to familiar names, naturalistic sounds or words having semantic associations e.g. doctor-nurse, hammer-nail) can trigger specific semantic associations. The second section of this dissertation focuses on the methodological aspects of semantic priming in the context of unfamiliar spoken words (such as unfamiliar, novel brand names) and explores the effect of different inter-stimulus intervals (ISI’s) (or stimulus onset asynchronies SOA’s) between an auditory prime and a visual target on the cross-modal perceptual enhancement. The results suggest that the most effective ISI between an unfamiliar word (such as a hypothetical brand name) and a phonetically congruent visual target (the associated graphical representation) is immediate onset and that as the SOA is reduced (i.e. as the stimuli overlap further), the priming effect too is reduced. These results contribute to the literature on cross-modal semantic priming by exploring the priming effect on spoken unknown words and demonstrate a maximal priming effect at an ISI of 0 ms in contrast to previous similar research (which has used known words and naturalistic sounds as primes). In sum, this dissertation reveals how sound symbolism operates at a phonetic level in the context of brand names and implicitly influences the way in which consumers conceive of a brand and it’s apparent status as a premium or basic good.